Case report of aggressive treatments for large-cell neuroendocrine carcinoma of the esophagus. (2019) - Nakao, Yosuke; Okino, Tetsuya; Yamashita, Yo-ichi; Taki, Katsunobu; Nakagawa, Shigeki; Matsumoto, Katsutaka; Goto, Mataro; Baba, Hideo
Highlights: Neuroendocrine carcinoma of the esophagus is a rare and highly aggressive disease. A case of large-cell neuroendocrine carcinoma of the esophagus in a 73-year-old male patient with aggressive surgical treatment. We performed subtotal esophagectomy, partial hepatectomy, radiotherapy and chemotherapy using cisplatin and irinotecan. We believe that aggressive treatment can become one treatment option with the aim of extending survival. Abstract: Introduction: Neuroendocrine carcinoma of the esophagus is a rare and highly aggressive disease, and the biological features are poorly understood. Presentation of case: We report a case of large-cell neuroendocrine carcinoma of the esophagus in a 73-year-old male patient with aggressive surgical treatment. Upper gastrointestinal endoscopy revealed an esophageal large mass. Histological examination of biopsy specimens indicated a neuroendocrine carcinoma. First, we performed subtotal esophagectomy with lymphadenectomy, but he experienced metastasis at the liver and rib 5 months later. Next, we performed partial hepatectomy and radiotherapy for rib metastasis, but he experienced metastasis at the left pulmonary hilar lymph node and sacral bone. Finally, we performed chemotherapy using cisplatin and irinotecan. Discussion: The therapeutic strategy for large-cell NEC of the esophagus is unestablished. Thus, accumulating the therapeutic results garnered from various treatment tools is considerably important. Conclusion: Aggressive multimodal treatments including surgery have a possibility to gain better survival in patients with large-cell NEC of the esophagus.